“Mr. Co-op”: How Ray Theisen Enhanced Cooperative and Community Values in the Chippewa Valley - Theisen, Esther (My University, 2018)
Ray Theisen’s life and career, particularly his 30-plus years as general manager of Consumers’ Co-op of Eau Claire, had a significant impact on Eau Claire community values, organizations, and businesses. This paper examines Theisen’s early life, service in the military during World War II, personal values, and business knowledge in order to explain his successes as a manager, as well as a respected community leader. It will also explore how consumer cooperatives function, and why certain principles, such as democracy and community, can be enhanced through a cooperative business model.
Keywords: Grocery trade--United States; Grocery trade--Wisconsin; Theisen, Ray; Consumers' Co-Op--Eau Claire, Wis.; Veterans--United States--Wisconsin